Implementation of the Knowledge Management in Facing Governance Crisis through Good Corporate Governance (GCG) Values (A Study in the Indonesian Bureau of Logistics in Central Kalimantan Regional Division) - Rina Herawati; Nurmita Sari; Karnida Retta Ginting (Wacana Journal of Social and Humanity Studies, 2021)
Knowledge Management is an important part of governance, particularly when the organization changes into a company. In managing company based on the National Committee on Governance Policy which has issued the guidelines for good corporate governance implementation in 2006, in a condition of competition and governance crisis, it requires GCG as a fundamental principle of company to face crisis, such as Covid-19 pandemic. GCG principles based on National Committee on Governance Policy (transparency, accountability, responsibility, independence, reasonableness, and equality) are required to achieve sustainability of corporate business by considering stakeholders. Research problem is the implementation of knowledge management in Good Corporate Governance (GCG) values in Indonesian Bureau of Logistics in Central Kalimantan Regional Division. A reason to choose research locus in Indonesian Bureau of Logistics in Central Kalimantan Regional Division is good implementation of corporate governance which is continuously improved and perfected in line with government assignment in the field of food and commercial business demand and commitment, to see whether or not GCG implementation in Indonesian Bureau of Logistics reaches regional division level, particularly in Central Kalimantan Regional Division.This study applied a combination of descriptive methodology and development study methodology. This research shows the result that knowledge management in GCG values has been applied in Indonesian Bureau of Logistics in Central Kalimantan Regional Division, as proven by 1) communication which is established well in every personnel in the office of Indonesian Bureau of Logistics in Central Kalimantan Regional Division,Â  2) decision making as an authority of top management, but the process of policymaking also involves every aspect in the company, and 3) wide access availability to information from knowledge assessed with high percentage by employees of Indonesian Bureau of Logistics in Central Kalimantan Regional Division.